Inwentarz realny średniowiecznych dokumentów pergaminowych i pieczęci z zespołu Monastica przechowywanych w Archiwum Akt Dawnych Diecezji Toruńskiej w Toruniu - Włodarski, Łukasz (Archiwa, Biblioteki i Muzea Kościelne, 2016)
The following inventory presents parchment documents and medieval impressions of seals stored in the Historical Archive of the Diocese of Toruń. It only includes the archival materials stored in the aforementioned archive. Its task is primarily to fulfil the role of information and aid and to facilitate any archival research. The list published here contains seven parchment documents and five sigils, which are the most valuable part in the collection of this institution. Currently, they form part of the Monastica collection, Benedyktynki Toruń series, Diplomata subseries; initially, they constituted a fragment of the archival collection located at St. James the Apostle Parish in Toruń. The description of the individual archival units consist of the following elements: the number of regesta, the place and date of issuing a document, the regesta of a document in Polish, the current reference code, the physical description of a document, the actual condition of a document, previous editions and the description of seal impressions.